Anodic-potential-tuned bioanode for efficient gaseous toluene removal in an MFC. (10th April 2021) - You, Juping; Chen, Han; Xu, Liangliang; Zhao, Jingkai; Ye, Jiexu; Zhang, Shihan; Chen, Jianmeng; Cheng, Zhuowei
Highlights: Bioanode regulated by -0.35 V showed the best performance for toluene degradation. The regulated MFC showed a high coulomb efficiency for the toluene removal. The applied anodic potential did not obviously affect microbial community. The applied anodic potential changed the electron transfer pathway in the bioanode. Abstract: Microbial fuel cell (MFC) is an innovative technology to stimulate the anaerobic degradation of hydrocarbons and recover their chemical energy. Typically, for the hydrocarbon oxidation, its performance depends upon the activity of the bioanode. In this work, four anodic potentials pertained to the redox of four different membrane proteins of the microbes, namely -0.52, -0.35, -0.16, and 0.17 V vs. Ag/AgCl, were applied to tune the bioanode. Experimental results revealed that, the more negative the bioanode potential was, the more obvious the enhancement became. The biofilm tuned at -0.35 V exhibited a highest toluene removal efficiency of 99% (800 mg/m 3 ), and a maximum power density of 8.97 mW/m 2 with the Coulomb efficiency of 2.06%. The microbial community analysis indicated that the dominant microbes in the bioanode were Comamonas sp., Petrimonas sp., Sedimentibacter sp., Ignavibacterium sp. and Parachlamydia sp., which was almost unaffected by the applied anodic potentials. The cyclic voltammetry analysis showed that the bioanode tuned at 0.17, -0.16 and -0.35 V exhibited three completely different electron transfer pathways. Furthermore, three metabolic pathways with o -cresol as an intermediate were proposed under the four applied anodic potentials. These results demonstrated that the anodic potential acclimation offers an effective enhancement method for the gaseous toluene removal combined with power generation. Graphical abstract: Image, graphical abstract